2019
DOI: 10.1093/mnras/stz2058
|View full text |Cite
|
Sign up to set email alerts
|

Classifying exoplanet candidates with convolutional neural networks: application to the Next Generation Transit Survey

Abstract: Vetting of exoplanet candidates in transit surveys is a manual process, which suffers from a large number of false positives and a lack of consistency. Previous work has shown that Convolutional Neural Networks (CNN) provide an efficient solution to these problems. Here, we apply a CNN to classify planet candidates from the Next Generation Transit Survey (NGTS). For training datasets we compare both real data with injected planetary transits and fully-simulated data, as well as how their different compositions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 62 publications
3
17
0
Order By: Relevance
“…The initial fits to the NGTS data provided by revealed that the depths, widths and shapes of the transits for each object were compatible with transiting hot Jupiter planets. In addition, a convolutional neural network applied to the NGTS data found that the probabilities of each lightcurve containing a transiting exoplanet were all greater than 0.95, consistent with previous confirmed NGTS planet discoveries (Chaushev et al 2019).…”
Section: Ngts Discovery Photometrysupporting
confidence: 86%
“…The initial fits to the NGTS data provided by revealed that the depths, widths and shapes of the transits for each object were compatible with transiting hot Jupiter planets. In addition, a convolutional neural network applied to the NGTS data found that the probabilities of each lightcurve containing a transiting exoplanet were all greater than 0.95, consistent with previous confirmed NGTS planet discoveries (Chaushev et al 2019).…”
Section: Ngts Discovery Photometrysupporting
confidence: 86%
“…We also note that this system received a high planetary probability of 0.97 from a neural network trained to distinguish between transiting planetary systems and false positives in NGTS data (Chaushev et al 2019).…”
Section: Ngts Photometrymentioning
confidence: 82%
“…In this work, we explore a new approach to the interior characterization of exoplanets by employing a deep learning neural network to treat this inverse problem. In recent years, deep neural networks have been used in a number of exoplanetary science studies, with applications ranging from the detections of planetary transits (Pearson et al 2018;Shallue & Vanderburg 2018;Chaushev et al 2019) to atmospheric composition retrieval from measured planet spectra (Zingales & Waldmann 2018;Márquez-Neila et al 2018), and the computation of critical core and envelope masses of forming planets (Alibert & Venturini 2019). We approach the characterization of exoplanets by first creating a large dataset of synthetic planets and then training a multitask (Caruana 1997) mixture density network (MDN, Bishop 1994) to infer plausible thicknesses of the planetary layers using observables like mass and radius.…”
Section: Introductionmentioning
confidence: 99%